Fetal Central Nervous System Derived Extracellular Vesicles: Potential for Non-invasive Tracking of Viral Mediated Fetal Brain Injury - Goetzl, Laura; Stephens, Angela J.; Schlesinger, Yechiel; Darbinian, Nune; Merabova, Nana; Hillel, Miriam; Hirsch, Alec J.; Streblow, Daniel N.; Frias, Antonio E.; Roberts, Victoria H. J.; Haese, Nicole N.; Mani, Arunmani; et al. (Frontiers in Virology, 2021)
Introduction Extracellular vesicles derived from the fetal central nervous system (FCNSEs) can be purified from maternal serum or plasma using the protein Contactin-2/TAG1that is expressed almost exclusively by developing neurons in the hippocampus, cerebral cortex and cerebellum. We hypothesized that fetal CNSEs could be used to non-invasively detect and quantify viral mediated in-utero brain injury in the first trimester. Materials and Methods First trimester maternal samples were collected from a human clinical population infected with primary cytomegalovirus (CMV) and a non-human primate model of Zika (ZIKV) infection. In the CMV cohort, a nested case control study was performed comparing pregnancies with and without fetal infection. Cases of fetal infection were further subdivided into those with and without adverse neurologic outcome. ZIKV samples were collected serially following maternal inoculation or saline. All ZIKV cases had histopathologic findings on necropsy. Serum was precipitated with ExoQuick solution and FCEs were isolated with biotinylated anti-Contactin-2/TAG1 antibody-streptavidin matrix immunoabsorption. FCE Synaptopodin (SYNPO) and Neurogranin (NG) protein levels were measured using standard ELISA kits and normalized to the exosome marker CD81. Results Fetal CNSE SYNPO and NG were significantly reduced in cases of first trimester fetal CMV infection compared to those with infection limited to the mother but could not discriminate between fetal infection with and without adverse neurologic outcome. Following ZIKV inoculation, fetal CNSE SYNPO was reduced by 48 hours and significantly reduced by day 4. Discussion These data are the first to suggest that first trimester non-invasive diagnosis of fetal viral infection is possible. Fetal CNSEs have the potential to augment clinical and pre-clinical studies of perinatal viral infection. Serial sampling may be needed to discriminate between fetuses that are responding to treatment and/or recovering due to innate defenses and those that have ongoing neuronal injury. If confirmed, this technology may advance the paradigm of first trimester prenatal diagnosis and change the calculus for the cost benefit of CMV surveillance programs in pregnancy.